Internalization Of SAF Physical Assignment For Environment And Forestry In The Development Planning Of North Sumatera Province - Pambudi, Andi Setyo (JEKP (Jurnal Ekonomi dan Keuangan Publik), 2023)
Fiscal balance is intended to ensure balance and fairness in using financial resources between the central and regional governments so that regions have sufficient resources to meet local needs without neglecting national interests. Fiscal balance is also carried out in the environment and forestry sectors. To date, efforts to improve environmental quality and the carrying capacity of watersheds and lakes are still not in line with national expectations. The Special Allocation Fund (SAF) budget for the Environment and Forestry (E&F) Sector is encouraged to support the national priorities contained in the National Medium-Term Development Plan (MNDP) document and detailed in the Government Annual Work Plan (GAWP), with its implementation carried out by the Regional Government. This study aims to evaluate the internalization of the SAF Physical E&F Sector Menu in regional planning and assess the implementation of its utilization in the regions as input for future development planning in the environment and forestry sectors. This study uses a descriptive qualitative approach to ongoing evaluation through a literature review, questionnaires, and limited discussions (FGD) with regional stakeholders. The literature review used regional planning documents in 34 provinces, with a deep dive into North Sumatra Province. Based on the results of questionnaires, local governments argue that 71 percent of SAF has effectively achieved goals and objectives, while the remaining 29 percent is still not optimal. For the regions, the limited budget also causes low SAF effectiveness. The central and local governments must sit together to formulate the importance of increasing budget allocations in the Environment and Forestry field in the regions, increasing human resources capacity, improving coordination between relevant agencies, engaging relevant parties in conflict resolution, and improving monitoring and evaluation mechanisms.